Struktra organizacyjna i budowa organów kółek rolnych i ich związków: [Organizational framework and structure of the bodies of the agricultural circles and their unions] (Studia Prawnicze / The Legal Studies, 1963)
Agricultural circle is a main tool in restructuring the socio-economic relations in the Polish rural areas. As mass, voluntary, socio-economic peasant organizations, they develop activities which are diverse in content and form in the sphere of the agricultural economy and the needs of the countryside. There are three main functions of agricultural circles in this activity:• As an association of the individual agricultural producers and a representative of the agricultural business, they are a kind of form of the economic self-management in the peasant economy.• The agricultural circles perform tasks which characterize the activities of the service enterprises by managing the resources of the state fund intended for the purpose of raising and modernizing agriculture and by establishing the direct organization of the technical and economic services in the agricultural production.• As organizations (registered society), agricultural circles perform the public functions granted to them by the state and regarding all individual farms of the village.There is a close interdependence between the organizational framework and the structure of bodies for the implementation of their tasks; therefore, the above-mentioned main functions of the agricultural circles provide a platform for the legal analysis of their organizational framework as an essential basic element of the structural and legal solution.A thorough legal analysis of the framework and internal structure of the bodies of the agricultural circles and their unions (general meetings of members, boards and their presidiums, audit commissions) grants us the right to draw a general conclusion that they correspond to the basic provisions arising from the nature of the tasks carried out by the agricultural circles. However, some critical remarks on many particular provisions of the Charter arise.In particular, they concern:—          the procedure and method for electing the board members, selecting the personnel of these bodies appropriate for the task implementation and the influence of voters on their functioning during the term of their powers;—          the legal status of the general meeting as the most representative body of the agricultural circle but limited by the Charter in the control and evaluation of the activities of such executive and managing body as the board elected by it;—          the legal status of permanently functioning presidiums in the unions of the agricultural circles due to the tendencies for the allocation of so-called “narrower” or “closer” presidiums consisting of this category of members and making decisions on issues that, according to the Charter, should be decided by the presidium as a body within the meaning of the Charter;—          independence in relation to the controlled bodies of the audit commissions and thereby the subordination and extension of the control exercised by these commissions in the agricultural circles and their unions.Practice teaches us that legal definitions of the organizational framework adapted to social needs and tasks can greatly facilitate and accelerate the implementation of the intentions while inappropriate decisions hinder the social activity. The purpose of this article is to reveal and indicate only the general directions of socially necessary decisions in this area of social relations.